Effect of seawater on consistency, infiltration rate and swelling characteristics of montmorillonite clay - Mohie Eldin Elmashad; Alaa A. Ata (HBRC Journal, 2016)
This paper presents the results of an experimental investigation performed to quantify the effect of mixing clayey soils with saltwater on consistency and swelling characteristics of clays. Massive natural clay deposits and compacted clay backfills either exist or are used in certain important and sensitive applications such as dams, liners, barriers and buffers in waste disposal facilities. In many cases, the clay deposits in these applications are subjected to saltwater. However, in standard laboratory classification tests, distilled or potable water are usually used in mixing test samples. This may lead to faulty interpretation of the actual in-situ consistency and volume change behaviors. In this research, an attempt is made to quantify the changes in consistency and swelling of clay soils from various locations around the Nile valley and possessing a wide range of consistency, when mixed with natural seawater with different salt concentrations. The results showed that the increase of the salt concentration of the mixing water may result in major decrease in the liquid limit and swelling characteristics of high plasticity montmorillonite clays. The reduction in the swelling of the clay soils is also proportional to the rate of saltwater infiltration. In an attempt to correlate the swelling of clays to the rate of water infiltration, a new simplified laboratory apparatus is proposed where swelling and infiltration are measured in one simple test “the swelling infiltrometer”.